Non-intestinal type sinonasal cancers and exposure to occupational carcinogens: a case-control study - Bonzini, Matteo; Facchinetti, Nadia; Zanetta, Laura; Parassoni, Davide; Borchini, Rossana; Battaglia, Paolo; Turri-Zanoni, Mario; Castelnuovo, Paolo; Ferrario, Marco Mario (La Medicina del Lavoro, 2016)
Background: Sinonasal cancers are rare, often fatal, tumors with a very high proportion of cases attributable to occupational exposures. The relevance of different carcinogens deeply varies among histological subtypes, with intestinal type adenocarcinomas (ITAC) characterized by a very large proportion of workers exposed to wood dust. The role of occupation in the etiology of other histotypes is less clear and more disputed, with authors questioning the possible occupational origin of non-ITAC cancers. Methods: We conducted a hospital-based case-control study on 50 consecutives non-ITAC cancers and 50 controls, in Varese, Italy. Relative risks for previous exposure to carcinogens (any or single agent, i.e. wood/leather dust, solvents, metals) were calculated by multivariate logistic regression models adjusted for age, gender, smoking habits and residence (within or outside the Lombardy region). Results: Having been exposed to any occupational carcinogen carried an OR of 3.04 (95%CI: 0.91-10.21). Considering single carcinogens, we observed no increased risk for wood dust exposure (OR=1.02, 95%CI: 0.21-4.94), while a large effect associated with previous exposure to other recognized carcinogens (leather dust, solvents or metals) appeared: OR=7.01 (95%CI: 1.51-32.8). Discussion: Our results highlighted the importance of properly considering sinonasal cancers histological subtypes when investigating the role of occupational carcinogens. Grouping together all sinonasal cancers may end up in underestimating the role of wood in ITAC etiology as well as the relevance of other occupational exposures for non-ITAC tumors. All sinonasal cancers deserve a thorough investigation of the occupational history.